Emergence of Highly Multidrug-Resistant Bacteria Isolated from Patients with Infections Admitted to Public Hospitals in Southwest Iran - Namdari, Sepide; Farhadi, Ali; Khademalhoseini, Aida; Behzad-Behbahani, Abbas; Moaddeb, Afsaneh (Interdisciplinary Perspectives on Infectious Diseases, 2021)
Background. The emergence of multidrug-resistant (MDR) microorganisms causing infections is increasing worldwide and becoming more serious in developing countries. Among those, Acinetobacter species are becoming prominent. Objectives. The aim of this study was to determine the rate of antimicrobial resistance of the bacteria causing infections, Acinetobacter species in particular, in local public hospitals in Firuzabad, Fars province, Iran. Methods. This cross-sectional study was performed on different clinical specimens collected from patients who were suspected of infections hospitalized from March 2016 to March 2019 in local hospitals of Firuzabad, Fars province, Iran. The bacterial isolates were identified following standard microbiological methods. Clinical and Laboratory Standards Institute guidelines were used to identify the antibiotic susceptibility of these isolates. Results. Overall, 1778 bacterial etiologies were isolated from 1533 patients diagnosed with infection. Of these, 1401 (78.8%) were Gram-negative and the remaining were Gram-positive bacteria. Escherichia coli (37.1%), Klebsiella spp. (13.9%), and Acinetobacter species (10.4%) were the most common isolated bacteria. Antibiotic sensitivity testing in this study showed a high resistance rate of Acinetobacter species to all antibiotics tested except Colistin. During the study period, the rate of infection with highly multidrug-resistant Acinetobacter species increased from 7.2% to 13.3%. Conclusions. This study highlights the emergence of MDR bacterial agents such as Acinetobacter species as a new threat in our region. However, a decrease in the rate of infection with Pseudomonas aeruginosa was noticeable.